Searching for the Meaning of Zakat in the Qur'an: Paul Ricoeur's Hermeneutical Study of Symbols, Texts and Reinterpretations - Bidin, Bidin; Taufik Warman Mahfuzh; Syamhudian Noor (al-Afkar, Journal For Islamic Studies, 2025)
This study aims to examine the meaning of zakat in the Qur'an through Paul Ricoeur's hermeneutic approach with a focus on symbolism, text, and the process of refiguration. Through Ricoeur's hermeneutic theory, this study explores how zakat can be understood more deeply as a symbol of purification, social solidarity, and economic justice, and how the Qur'anic texts about zakat can be reinterpreted according to contemporary challenges and needs. This study uses a qualitative method with data collection techniques in the form of literature studies. The main data sources for this study are the verses of the Qur'an related to zakat, classical and contemporary interpretations, and literature on Paul Ricoeur's hermeneutics. The data were analyzed using Ricœur's hermeneutic approach which emphasizes understanding symbolism and the process of refiguring texts. The results of the study show that Paul Ricoeur's hermeneutic approach provides a new framework for understanding zakat. Zakat is understood not only as a financial obligation, but also as a symbol that reflects the values ​​of social justice and purification of the soul. Ricœur's theory of textual autonomy allows for a rereading of the zakat verses in a modern context, where challenges such as economic inequality and global poverty are increasingly pressing. The process of reinterpretation allows zakat to remain relevant and serve as an instrument of economic empowerment and wealth distribution in modern society.